1997
DOI: 10.1200/jco.1997.15.6.2231
|View full text |Cite
|
Sign up to set email alerts
|

Philadelphia chromosome in relapsed childhood acute lymphoblastic leukemia: a matched-pair analysis. Berlin-Frankfurt-Münster Study Group.

Abstract: It was shown that the Ph1 is indeed an independent risk factor in childhood relapsed ALL. There are striking similarities between these patients and children at initial diagnosis, as well as adult patients. Therefore, it is highly suggestive that the Ph1 is also an independent risk factor under all of these circumstances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 24 publications
0
20
0
2
Order By: Relevance
“…Clinical studies have shown that the Philadelphia chromosome translocation, t(9;22)(q34;q11), is an independent risk factor in childhood ALL (23). At the molecular level this results in the fusion of Bcr and Abl sequences leading to a chimeric mRNA and the Bcr-Abl protein.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have shown that the Philadelphia chromosome translocation, t(9;22)(q34;q11), is an independent risk factor in childhood ALL (23). At the molecular level this results in the fusion of Bcr and Abl sequences leading to a chimeric mRNA and the Bcr-Abl protein.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 14 patients with no hematological relapse (74%), eight remained BCR-ABL negative for up to 4 years and six had no molecular follow-up (five of them died in the first 3 months after HSCT). Five patients (26%) experienced a relapse, all after transient negativity of RT-PCR, and BCR-ABL transcript reappearance at 3,8,17,20, and 43 months. Three patients were treated with chemotherapy without interferon-a, but with DLI in two cases.…”
Section: Minimal Residual Disease Follow-upmentioning
confidence: 99%
“…There were 63 males and 58 females who had received HSCT in 27 centers. Two groups were analyzed: 102 adults with a median age of 38 years (range, 18-53) and 19 children with a median age of 8 years (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Median white blood cell count (WBC) was 19 Â 10 9 /l (range, 1-500) for the entire population, 36 Â 10 9 /l (range, 1-382) in children, and 18 Â 10 9 /l (range, 1-500) in adults.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Patients with Ph+ ALL have an extremely poor prognosis for long-term survival. 4 Although the ability to achieve a first complete remission (CR) is not significantly reduced in Ph+ ALL, the durability of these remissions with standard and intensified chemotherapy regimens is extremely limited. 5 Allogeneic bone marrow transplantation (BMT) has been utilized as a post-induction therapy to try to improve disease-free survival (DFS) for these patients.…”
Section: Introductionmentioning
confidence: 99%